Experimental and theoretical investigations on kinetic mechanisms of low-pressure CO2 adsorption onto Malaysian coals - Abunowara, M. (Elsevier B.V., 2021)
The adsorption mechanism of carbon dioxide (CO2) in the coal matrix is significant in practical stability and migration process of CO2 into a coalbed seam. This study presents the kinetic investigation and the main controlling step of CO2 adsorption capacity onto Malaysian coals. The experimental data of CO2 adsorption were determined using a volumetric technique at 273, 298, 308, and 318 K and pressures up to 99.3 kPa. The experimental data of CO2 adsorption was studied using kinetic based thermodynamic models. Fourier Transform Infrared Spectroscopy and XâRay Diffraction analyses were performed for the coal samples characterization. The major functional group in all coal samples is hydroxyl (âOH) functional group. XâRay Diffraction analysis has shown that the coal samples possessed one major peak assigned to quartz (d = 3.348 Ã ). The experimental results were correlated using kinetic models, which include pseudoâfirstâorder, pseudoâsecondâorder, Avrami, and Intra-particle diffusion models. The Intraâparticle diffusion model was found in the best compliance with the experimental data. Therefore, the poreâdiffusion is considered to be the primary limiting step for CO2 interaction with the coal matrix. This indicated that the molecules of CO2 transferred rapidly from the bulk to the surface of coal matrix and slowly diffused into pores of the coal matrix. The obtained results demonstrated that the overall CO2 interaction with the coal matrix is influenced by the diffusion limiting step. The value of activation energies for all studied coal samples is lower than 8 kJ/mol. This showed that CO2 adsorption onto all investigated coal samples is driven by a physical adsorption process. Â© 2021 Elsevier B.V.